Transcriptomic analysis of the liver in aged laying hens with different eggshell strength - G.P. Han; J.H. Kim; J.-M. Kim; D.Y. Kil (Poultry Science, 2023)
ABSTRACT: Eggshell is composed of a very ordered and mineralized structure and is important for egg quality. Eggshell strength is particularly important because of its direct association with economic outcomes and egg safety. Various factors related to laying hens and their environment affects eggshell strength. However, the molecular mechanisms of liver functions related to decreased eggshell strength of aged laying hens are largely unknown. Therefore, this study aimed to identify potential factors affecting eggshell strength in aged laying hens at the hepatic transcriptomic level. A total of five hundred 92-wk-old Hy-line Brown laying hens were screened to select those exhibiting the greatest variation in eggshell strength. Based on the final eggshell strength, 12 hens producing eggs with strong eggshell strength (SES) and weak eggshell strength (WES) were finally selected (n = 6) for liver tissue sampling. The RNA-sequencing was performed to identify differentially expressed genes (DEGs) between the 2 groups. We identified a total of 2,084 DEGs, of which 1,358 genes were upregulated and 726 genes were downregulated in the WES group compared with SES group. According to the Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis, the DEGs indicated the mammalian target of rapamycin signaling pathway, the Janus kinase-signal transducer and activator of transcription pathway, the mitogen‑activated protein kinase signaling pathway, and the insulin resistance pathways. Genes related to fatty liver disease were upregulated in WES group compared with SES group. In addition, expression of several genes associated with oxidative stress and bone resorption activity was altered in aged laying hens with different eggshell strength. Overall, these findings contribute to the identification of genes involved in different intensity of eggshell strength, enabling more understanding of the hepatic molecular mechanism underlying in decreased eggshell strength of aged laying hens.